2019
DOI: 10.1186/s13104-019-4126-2
|View full text |Cite
|
Sign up to set email alerts
|

Psychotropic medication non-adherence among patients with severe mental disorder attending at Bahir Dar Felege Hiwote Referral hospital, north west Ethiopia, 2017

Abstract: Objective Medication non-adherence is a major public health problem that has been called an “invisible epidemic”. Globally, non-adherence rates among patients with severe mental illness ranged between 30 and 65%. It greatly increases the risk of illness exacerbation and hospitalizations. However, there is a paucity of studies examining treatment non-adherence and its associated factors among patients with severe mental disorder. Therefore, this study was aimed at determining the magnitude of medic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
20
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 25 publications
(31 reference statements)
5
20
3
Order By: Relevance
“…In our study finding, 55 (18.3%) had poor social supports whereas 39 (13.0%) of them had high social supports. A closely related finding was reported by Gebeyehu et al where 45.9% had good social support [29]. Living with kids and spouses was negatively associated with self-stigma up on multivariable linear regression.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…In our study finding, 55 (18.3%) had poor social supports whereas 39 (13.0%) of them had high social supports. A closely related finding was reported by Gebeyehu et al where 45.9% had good social support [29]. Living with kids and spouses was negatively associated with self-stigma up on multivariable linear regression.…”
Section: Discussionsupporting
confidence: 85%
“…Contrary to this, the prevalence was higher than in India 26% [ 58 ] and Addis Ababa, Ethiopia (26.5%) [ 42 ]. The finding was also lower than a study conducted in Nigeria (48.0%) [ 59 ], Curitiba, Parana (49%) [ 60 ], Nigeria 54.2% [ 61 ], Bahir Dar, Ethiopia (55.2%) [ 29 ], South Africa 63.2% [ 62 ] and Pakistan’s study (64.75%) [ 63 ]. This variation could be due to the differences in socio-demography of the study population, selection criteria for the study participants, study design, sample size and tools used for the assessment of adherence.…”
Section: Discussioncontrasting
confidence: 60%
See 2 more Smart Citations
“…In our study, the 111(31.65%) of participants were non-adherent to their medication and this result was higher than study conducted at Ayder Referral Hospital, Mekelle, Northern Ethiopia which revealed 26.5% of patients with schizophrenia were non-adherent to their antipsychotic medication [29] and the result was lower than finding of the study conducted at Bahir Dar Felege Hiwote Referral hospital, northwest Ethiopia which revealed overall prevalence of medication non-adherence was 55.2% [30] This difference could be due to the different tools used to measure medication non-adherence. The lowest score on the social relationship domain of QoL among people with schizophrenia in our study could be due to the negative symptoms, which affect the patient's ability to live independently, to perform activities of daily living, to be socially active and maintain personal relationships.…”
Section: Discussioncontrasting
confidence: 70%